2012
DOI: 10.1136/bmj.d7962
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A supplementation in preschool children and risk of hearing loss as adolescents and young adults in rural Nepal: randomised trial cohort follow-up study

Abstract: Objective To determine whether vitamin A supplementation administered in the preschool years can lower the risk of hearing loss in adolescence and adulthood.Design Follow-up study of adolescents and young adults who, as preschool aged children in 1989, were enrolled into a cluster randomised, double blinded, placebo controlled trial of vitamin A supplementation. Setting South central, rural Nepal.Participants 2378 adolescents and young adults aged 14 to 23, representing 51% of those who finished the original t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 40 publications
(43 reference statements)
0
31
0
Order By: Relevance
“…The colostrum discarded usually results in failure to maintain normal vitamin A levels among infants. One recent study confirmed the role of high dose of vitamin A supplementation to significantly reduce progressive hearing loss associated with purulent ear infections in early childhood (18). …”
Section: Introductionmentioning
confidence: 88%
“…The colostrum discarded usually results in failure to maintain normal vitamin A levels among infants. One recent study confirmed the role of high dose of vitamin A supplementation to significantly reduce progressive hearing loss associated with purulent ear infections in early childhood (18). …”
Section: Introductionmentioning
confidence: 88%
“…This subcohort had participated as preschoolers in a placebo-controlled vitamin A supplementation trial in 1989–91 (22) and were followed in an ear health and hearing survey from 2006–2008 (23). …”
Section: Methodsmentioning
confidence: 99%
“…Wald p -values were reported for categorical variables. Due to our previously reported effect of vitamin A allocation reducing hearing loss attributed to otitis media (23), interaction by childhood trial allocation to vitamin A vs placebo was assessed in the linear regression model and was not found to be present.…”
Section: Methodsmentioning
confidence: 99%
“…In chronically undernourished populations, vitamin A supplementation during pregnancy has been associated with decrease hearing loss due to ear infections in the offspring [31] and improved growth outcomes [32]. Supplementation of vitamin A during pregnancy in an undernourished population in Nepal has also been associated with improved offspring lung function [33], however; it did not decrease risk of asthma [34].…”
Section: Vitamin a Compounds And Infant Feedingmentioning
confidence: 99%